Change in microbiota profile after vaginal estriol cream in postmenopausal women with stress incontinence - Moore, Kate H.; Ognenovska, Samantha; Chua, Xin-Yi; Chen, Zhuoran; Hicks, Chloe; El-Assaad, Fatima; te West, Nevine; El-Omar, Emad (Frontiers in Microbiology, 2024)
Vaginal estrogen is a treatment for genitourinary symptoms of menopause (GSM), which comprises vaginal atrophy and urinary dysfunction, including incontinence. Previous studies show that estrogen therapy promotes lactobacilli abundance and is associated with reduced GSM symptoms, including reduction of stress incontinence. However, detailed longitudinal studies that characterize how the microbiome changes in response to estrogen are scarce. We aimed to compare the vaginal microbiota of postmenopausal women, before and 12 weeks after vaginal estrogen cream.Methods: A total of 44 paired samples from 22 postmenopausal women with vaginal atrophy and stress incontinence were collected pre-vaginal estrogens and were compared to 12 weeks post-vaginal estrogen. Microbiota was characterized by 16S rRNA amplicon sequencing and biodiversity was investigated by comparing the alpha-and beta-diversity and potential markers were identified using differential abundance analysis.Results: Vaginal estrogen treatment was associated with a reduction in vaginal pH and corresponded with a significant reduction in alpha diversity of the microbiota. Healthy vaginal community state type was associated with lower mean pH 4.89 (SD=0.6), in contrast to dysbiotic state which had a higher mean pH 6.4 (SD=0.74). Women with lactobacilli dominant community pre-treatment, showed stable microbiota and minimal change in their pH. Women with lactobacilli deficient microbiome pretreatment improved markedly (p=0.004) with decrease in pH -1.31 and change to heathier community state types.In postmenopausal women with stress incontinence, vaginal estrogen promotes Lactobacillus and Bifidobacterium growth and lowers vaginal pH. Maximum response is seen in those with a dysbiotic vaginal microbiota pre-treatment.